FAKTOR-FAKTOR YANG MEMPENGARUHI KEUNGGULAN BERSAING DALAM UPAYA MENINGKATKAN KEPUTUSAN PEMBELIAN - Lenggogeni, Laylani; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2016)
Intense business competition has made decreasing costumer of PT. Sinar Mas at Tugu Ibu Hospital, West Java for the past 3years. for the past 3 years, PT. Sinar Mas has the costumer decreasing at Tugu Ibu Hospital due to intense business competition in indonesia assurance company. PT. Sinar Mas is one of leading assurance company in indonesia with good reputation.Â The purpose of this research is determine the influence of variable competitive price, service quality, and personal selling to increasing the purchase decision of PT. Sinar Mas. competitive price, service quality, and personal selling as independent variables; competitive advantage as variable intervening; and purchase decision as dependent variable. Population used for this reseacrh are patient and employee who interested or having an experience using health assurance at rs tugib. This research method using a non-probability sampling technique by purposive sampling method. Used as a sample 100 respondents. Data obtained from the questionnaire which is then processed and analyzed using SPSS. The results showed that all three of independently variable has a positive influence on competitive advantage; and competitive advantage have a positive influence on the buying decision. Of the three independent variables influence the service quality has the greatest impact on brand image, and the smallest is the Competitive Price.